2022
DOI: 10.1093/jalm/jfac028
|View full text |Cite|
|
Sign up to set email alerts
|

Point-of-Care: Roadmap for Analytical Characterization and Validation of a High-Sensitivity Cardiac Troponin I Assay in Plasma and Whole Blood Matrices

Abstract: Background High-sensitivity cardiac troponin (hs-cTn) assays enable more precise use of traditional diagnostic strategies and earlier rule-out/rule-in at 0/1 h or 0/2 h after presentation of acute myocardial infarction (AMI). Availability of hs-cTn measurements at point-of-care (POC) can improve timely management of AMI patients. A roadmap for regulatory and analytical validation is exemplified with studies with the Atellica VTLi hs-cTnI at POC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The turn-around time from the application of the droplet of blood to the test result is approximately 8 min. The limit of detection is 1.6 ng/L and the limit of quantitation is 8.9 ng/L (at 10% CV) and 3.7 ng/L (at 20% CV) 22. The 99th percentile overall, for men and for women are, respectively, 23, 27 and 18 ng/L.…”
Section: Methods and Analysismentioning
confidence: 91%
“…The turn-around time from the application of the droplet of blood to the test result is approximately 8 min. The limit of detection is 1.6 ng/L and the limit of quantitation is 8.9 ng/L (at 10% CV) and 3.7 ng/L (at 20% CV) 22. The 99th percentile overall, for men and for women are, respectively, 23, 27 and 18 ng/L.…”
Section: Methods and Analysismentioning
confidence: 91%
“…Recent analytical data have demonstrated that whole-blood and lithium-heparin plasma results correlated well in serial specimens from patients presenting to the ED. 23 We also acknowledge the need for future studies to address any potential bias or difference between plasma and whole-blood measurements that may or may not be clinically meaningful at concentrations close to the rule-out threshold. The present study supports the use of this hs-cTnI POC assay to facilitate early safe discharge without admission or urgent cardiac testing 1 but not in early presenters.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh EDTA plasma and lithium-heparinized whole blood were concurrently measured: plasma on the clinically used hs-cTnI Abbott ARCHITECT i2000 SR analyzer 9,10 and whole blood on the hs-cTnI Siemens POC Atellica VTLi investigational assay. 22,23 The POC testing was performed by the same laboratory staff for both assays. The ARCHITECT hs-cTnI sex-specific 99th percentile upper reference limits (URLs) were 16 ng/L for female patients and 34 ng/L for male patients.…”
Section: Derivation Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathfast and Triage lack studies on their clinical performance in AMI rule-in and rule-out. The most promising is the Atellica VTLi, with its analytical performance rigorously assessed in plasma and whole blood [ 79 ]. The Atellica’s clinical performance has been derived and validated in a US cohort (whole blood, n = 1086) against the Abbott hsTnI and in Australia (plasma, n = 1486) against the Beckman hs-cTnI [ 80 ].…”
Section: Clinical Considerations For Hs-ctn To Rule In and Rule Out Amimentioning
confidence: 99%